Relational Obligations: Defending a Non-Voluntarist Argument for Special Responsibilities - Farmer, Thomas Jared (Stance: an international undergraduate philosophy journal, 2019)
This paper attempts to demonstrate that special responsibilities exist as a necessary and fundamental component of relationships. It seeks to show that, while special responsibilities may be superseded by other relevant concerns, they remain absolute. The paper attempts to demonstrate further that, even in cases of repugnant conclusion, special responsibilities exhibit a residual nature. It argues that such obligations are not always voluntary entered, but nevertheless represent prima facie duties to those parties involved.